Different Support Programs Offered By Selected Financial Institutions and Its Impact on the Sustainability of Small Businesses - Teh, Cherry Rafer; Duguran, R-Jay C.; Lahin, Rick Rhine A.; Laque, Jame Paul A.; Traya, Roleto M.; Ugsod, Almie James O. (Research Journal in Business and Economics, 2025)
Support programs offered by financial institutions play a crucial role in helping small businesses grow and sustain operations, particularly in areas with limited access to capital, training, and essential business tools. These programs are designed not only to provide financial aid but also to enhance the skills, knowledge, and operational capabilities of small business owners. This study investigates how such support programs, particularly financial ones, influence the long-term success, stability, and performance of small businesses located in resource-limited communities. The research focuses on 15 owners of small retail businesses associated with selected financial institutions. The main objective of this study is to determine whether the support programs offered by these institutions effectively contribute to the sustainability and overall success of small businesses. Data were collected through structured survey forms distributed to participating business owners. The gathered responses were analyzed using both descriptive and inferential statistical methods. Descriptive statistics, including means and standard deviations, were employed to assess the participants’ satisfaction with the support programs. For deeper analysis, inferential tools such as the independent sample t-test and one-way ANOVA were utilized to examine whether significant differences existed in business sustainability based on factors such as number of years in the business, average monthly income, and type of business. Pearson’s r correlation was also used to identify the relationship between satisfaction with the support programs and business sustainability. The results revealed an average satisfaction score of 3.29, indicating that business owners were somewhat satisfied with the assistance received. However, the findings also showed that, despite their appreciation, the support programs had minimal impact on business performance and sustainability. The relationship between satisfaction and outcomes such as profit, customer growth, and stability was weak or statistically insignificant. Furthermore, business-related factors such as length of operation, investment size, and workforce did not significantly affect business sustainability levels. These results suggest that current support programs may not fully address the evolving needs of small retail enterprises. While such programs temporarily boost morale, long-term success requires business owners to continuously develop skills, innovate, and provide consistent value to customers.